Pengembangan Modul Pembelajaran Biologi Berbasis Pendekatan Saintifik Untuk Meningkatkan Hasil Belajar Siswa - Muhammad Wahyu Setiyadi (Journal of Educational Science and Technology (EST), 2017)
The purpose of this study was to develop a scientific-based learning module on a valid ecological concept, practical and effective to the students of Senior High School. The development procedures of the research employed Thiagarajan Model or 4-D Model which consisted of four stages, namely defining, design, development, and dissemination. The data were collected through learning module validation process, students and teachers' responses questionnaire, learning implementation observation sheet, and learning result test. The data were analyzed by using descriptive analysis. The results of the research reveal that Biology learning module based on scientific approach is valid, practical, and effective. It is stated as valid because Biology learning module based on scientific approach which is developed had met validity criteria with "Valid" category. It is stated as practical because the learning implementation by using Biology learning module based on scientific approach had learning implementation in high category, and students and teachers positive responses on the module. It is stated as effective because it had fulfilled effectiveness namely the students' learning result test had met classical completeness criteria by 84.21%.